Intelligent Monitoring of Disinfectants - Kumar D.; Mishra A.; Chaudhri S.N.; Rajput N.S. (My University, 2025)
Spraying disinfectant is a crucial concern for the hygiene of workplaces (e.g., hospitals, offices, and homes). Its improper and irregular use causes the risk for several health issues (e.g., infection, eye & skin irritation, itching, etc.). Hence, disinfection and hygiene are two integral parts of local safety measures within the basic guidelines for healthcare. The importance of disinfectants gained much attention during the recent pandemic (COVID-19). Quality sanitization requires proper usage of disinfectant concentration at regular time intervals. Therefore, monitoring disinfectant type is crucial. In this paper, we have proposed a gas sensor array-based monitoring system to achieve the mentioned objective. We have considered a real-field setup in our laboratory for database collection. It has sensor responses of seven commercial liquid disinfectants. This database contains the exposure of each disinfectant for 30 min, present individually. Further, we have applied various machine learning algorithms and compared their performances on different metrics. Overall, this research aims to develop an intelligent disinfectant monitoring system. © 2023, The Author(s), under exclusive license to Springer Nature Switzerland AG.